Gingival Overgrowth on Chronic use of Amlodipine: A Case Report - Peedikkal, Muhammed Rashid Parambil; Sebastian, Juny; Ramesh, Madhan; Doddaiah, Narayanappa; Prashanth, Sathya Narayana (Indian Journal of Pharmacy Practice)
Background: Amlodipine, a calcium channel blocker (CCB) which is a commonly prescribed antihypertensive medication. Nifedipine is the CCB which is most frequently associated with drug induced gingival overgrowth. Case report: A 9 year old girl presented to the out-patient department of the hospital with the complaints of swelling of left side of cheek with mild to moderate grade pain since 5-6 days.The pain increased on touching and during jaw movements. Her past medical history revealed that she was a known case of cardiomyopathy with bilateral renal artery stenosis with hypertension and was on oral medications amlodipine (5 mg BD), furosemide (40 mg BD) and carvedilol (3.125 mg BD) for the past three years. She was diagnosed as having gingival overgrowth induced by the use of amlodipine. The gingival overgrowth was managed with dental extraction, drainage of abscess and gum cartilage following the withdrawal of the offending drug amlodipine. Alternatively she was started on oral prazosin (1 mg BD) along with other regular medications. Conclusion: Though the incidence of amlodipine causing the gingival overgrowth is less when compared to other drugs in the CCB class, the patients have to be monitored for the gingival overgrowth when on chronic use.
Keywords: Amlodipine; Calcium channel blocker; Gingival overgrowth; Gum hyperplasia